Illocutionary Analysis of PPPA Minister’s Press Response to Bekasi Train Accident - Selvyana Angel br. Hombing; Apriliani Putri Br Aruan; Saskia Indah Prabudi; Putri Balqis Nazilah; Dian Marisha Putri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study analyzes the illocutionary speech acts found in the statements of the Minister of Women’s Empowerment and Child Protection regarding the Bekasi commuter train accident. The objectives of this study are to identify the types of illocutionary acts used in the Minister’s spontaneous interview responses and clarification statements, analyze their functions based on John Searle’s classification, and examine how the context of public communication influences meaning construction. This research employs a qualitative descriptive method, with data collected from television interviews, press statements, and clarification posts uploaded through the Minister’s official social media account. The findings reveal that assertive acts are the dominant type, appearing 3 times (37.5%), followed by directive and expressive acts with 2 occurrences each (25%), and commissive acts with 1 occurrence (12.5%), while no declarative acts were identified. The dominance of assertive acts indicates that the Minister mainly used language to provide explanations, clarification, and factual information regarding the incident and the related policy response. In addition, directive acts functioned to offer suggestions and encourage collective awareness, expressive acts conveyed sympathy and apology, and commissive acts reflected institutional commitment toward the victims. The study also shows that spontaneous interviews and clarification statements create different patterns of meaning construction, where spontaneous responses tend to be more immediate and less structured, while clarification statements appear more formal and controlled. Therefore, this study confirms that language in public communicationfunctions not only as a means of conveying information but also as a social act that shapes public perception and institutional credibility in crisis situations.Keyword: Illocutionary Acts, Speech Act, Press Response, Spontaneous Interview, Accident Discourse